3d-QSAR Of Biphenyl Analogues As Anti-Inflammatory Agents By Genetic Function Approximation (GFA) (Part-II) - UJASHKUMAR A. SHAH; NILESH K. WAGH; HEMANTKUMAR S. DEOKAR; SHIVAJIRAO S. KADAM; VITHAL M. KULKARNI (International Journal of Pharma and Bio Sciences, 2010)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used for the treatment of pain, fever and inflammatory diseases such as rheumatoid arthritis and osteoarthritis. A series of direct analogues of flurbriprofen [4’-methylbiphenyl-2-(substituted phenyl) carboxamide derivatives] have been reported as novel anti-inflammatory agent. In order to gain further insights into the structural requirements of novel this series of direct analogues of flurbriprofen, a three-dimensional quantitative structure activity relationship (3D-QSAR) was performed using Genetic Function Approximation (GFA). The QSAR models revealed the importance of thermodynamic, structural and electronic parameters. The internal predictivity (r2) and external predictivity (r2pred) of final QSAR model was 0.66 and 0.60 respectively. Analysis of results from the present QSAR study indicates that thermodynamic, structural and electronic parameters strongly govern the antiinflammatory which can give further guidance for design of potent anti-inflammatory agents.